ANALYSIS OF THE THREAT OF THE SPREAD OF INTIMATE CONTENT NON CONSENSUAL IN VIOLENCE GENDER BASED ONLINE - Prayudati, Yulia Martha; Trisna, Wessy; Sharfina Desiandri, Yati (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This journal discusses the phenomenon of Online Gender-Based Violence (OGBV) which is increasingly worrying in the digital era, especially related to the spread of non-consensual intimate content (NCII) or what is often referred to as "revenge porn." This study explores the factors that cause NCII, including abuse of trust, unsafe use of technology, and weak legal regulations. OGBV, as a form of gender-based violence, has profound psychological, social, and economic impacts on victims, including trauma, stigma, and career losses. In addition, this journal also discusses the prevention and protection efforts needed, such as increasing digital literacy, strengthening regulations, and collaboration between various stakeholders. It is hoped that with stronger measures, the threat of the spread of non-consensual intimate content can be minimized and protection for victims can be increased.